Dose-Dependent Effects of Di-(2-Ethylhexyl) Phthalate (DEHP) in Mussel Mytilus galloprovincialis - Hai’e Xu; Hai’e Xu; Wanshuang Cao; Hongliang Sun; Shougang Zhang; Pan Li; Surong Jiang; Caiyun Zhong (Frontiers in Marine Science, 2021)
Phthalic acid esters (PAEs) are environmental organic pollutants that are ubiquitous in the ocean, and di-(2-ethylhexyl) phthalate (DEHP) is the most widely used PAE. The environmental concentration of DEHP was reported to be up to 42.52 μg/L in seawater in the estuaries located in Jiaozhou Bay along the Yellow Sea. DEHP has been investigated with respect to its toxicity in marine organisms. However, evidence on the dose-dependent effects of DEHP remains contradictory and limited. We used marine mussel Mytilus galloprovincialis as the experimental animal to study the dose-dependent effects of various levels of exposure to DEHP (concentrations of 4, 12, 36, 108, and 324 μg/L). These effects and the underlying mechanisms were elucidated by the levels of antioxidant enzyme activity, gene expression, and metabolite. The results indicated that, at environmentally relevant concentrations (12 and 36 μg/L), DEHP induced significant hormetic effects. This was indicated by the U-shaped or inverted U-shaped responses of the gene expression levels related to stress response (CAT, GST, and MgGLYZ) and antioxidant enzyme activities (SOD and CAT). The metabolic profiles revealed that DEHP generally caused monophasic response in osmotic regulation (homarine) and biphasic response (hormesis) in energy metabolism (glucose, glycogen, and amino acids), respectively. These findings can aid in ecological risk assessment with respect to DEHP and the determination of hormetic dose responses.